This is Metacognition (Docentes 2.0 Journal, 2025)
To understand metacognitive development, it is essential to explore and analyze the contributions of various theorists who have proposed various channels and guidelines through which human learning develops. The purpose of this study was to deeply immerse themselves in the various theories and concepts about metacognition proposed by scholars through research, ranging from self-regulation and cognitive control to the ability to reflect and monitor one's learning strategies. This essay was framed under the inductive method in the humanistic paradigm, with a qualitative approach of an interpretive type and a narrative topic design. In the study, it was made evident in a series of practical exercises in the development of a partial form in several phases; in the discovery of applied learning to young adolescents in secondary school grade school, their abilities and skills can be observed, as well as the difficulties presented in their development. In conclusion, by integrating these approaches into the design of educational activities, the challenges posed by learning theory are effectively met, and the development of advanced cognitive skills is contributed to. The approach is humanistic, based on the idea that learning should allow students to become critical and reflective individuals capable of transforming social reality.
Keywords: Metacognition; tic tac toe; knowledge; know-how